Analisis Syariah Terhadap Praktik Trading Forex Online: Identifikasi Masalah Dan Solusi - Putri, Elen Sri Ega; Assyifa, Zubaidah (EL-EMIR Institute, 2024)
This study aims to conduct an in-depth analysis of online forex trading practices from a sharia perspective. This research uses qualitative research methods as its main design, which has a very important role in this research. In research regarding sharia analysis of online forex trading practices, the research method used involves a qualitative approach. This approach was chosen because this research aims to understand and analyze concepts, views and interpretations from an Islamic sharia perspective regarding forex trading. The results of this study show that although there are various challenges in ensuring sharia compliance in online forex trading, solutions such as swap-free accounts, education, transparency and careful use of leverage can help overcome these problems. Muslim traders must be careful in choosing brokers and trading strategies that comply with sharia principles to ensure that their trading activities are halal and ethical.